Socioeconomic factors, perceived stress, and social support effect on neonatal nurse burnout in China: a cross-sectional study - Zhen-peng Huang; Fang Huang; Qun Liang; Feng-zhen Liao; Chuan-zhuang Tang; Min-lan Luo; Si-lan Lu; Jing-jing Lian; Shan-e Li; Su-qiao Wei; Bin Wu (BMC, 2023)
Abstract Background Neonatal nurses' working environments are highly stressful, and burnout is common. This study examines the effect of socioeconomic factors, perceived stress, and social support on neonatal nurse burnout. Methods A total of 311 neonatal nurses participated in this study. They were administered a validated Maslach Burnout Inventory. The study employed a 14-item perceived stress scale (PSS-14) and a social support rate scale (SSRS) to examine stress, socioeconomic factors, and lifestyles. Results Of the neonatal nurses, 40.19% had burnout, 89.60% had mild burnout, and 10.40% had moderate burnout; no neonatal nurse experienced severe burnout. Young nurses and those with low technical skills, poor interpersonal relationships, irregular diet, and insufficient rest were exposed to burnout (all p < 0.05).Most burnout nurses experienced moderate-severe perceived stress, and their PSS-14 scores were higher (all p < 0.05).The scores for objective social support, subjective social support, utilization of social support, total SSRS scores, and the level of social support were all lower in burnout nurses (all p < 0.05). Perceived stress was correlated positively and significantly with emotional exhaustion and personal accomplishment (all p < 0.05). Social support correlated significantly with and reduced personal accomplishments (p < 0.05). Age, poor interpersonal relationships, perceived stress, and social support were all independent factors associated with neonatal nurse burnout (all p < 0.05). Conclusion The prevalence of burnout in neonatal nurses was higher than average. Socioeconomic factors, higher perceived stress, and lower social support contribute to neonatal nurse burnout. Nursing managers should pay attention to socioeconomic factors, perceived stress, and social support among neonatal nurses and employ strategies to reduce neonatal nurse burnout.